2016
DOI: 10.1002/ente.201600107
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Upgrading Lignin Pyrolysis Vapors by Ex Situ Catalytic Fast Pyrolysis

Abstract: Lignin, a highly branched, substituted, mononuclear aromatic polymer, is one of the principal components of lignocellulosic biomass. Its valorization is considered an important part of the modern biorefinery scheme. However, as a result of the natural complexity and high stability of lignin, its depolymerization and the following conversion are challenging. The unique structure and composition of lignin offer many possible routes to produce liquid fuels and chemicals. Recognized as an efficient and feasible pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 166 publications
(150 reference statements)
0
16
0
Order By: Relevance
“…While non-basic nitrogen compounds and condensed aromatics contribute to coke formation on the external surface of zeolite crystallites and pore blockage [54], the poisoning ability of bulkier nitrogen bases is even higher [52,55]. Xu et al [56][57][58][59][60] demonstrated that N-heterocycles (pyridines, pyrroles, anilines and indoles) can be produced via reaction of biomass derived oxygenates and ammonia. Even though not measured directly, some ammonia may be produced from the FP of wheat straw containing ∼1 wt% N (d.b.)…”
Section: Discussionmentioning
confidence: 99%
“…While non-basic nitrogen compounds and condensed aromatics contribute to coke formation on the external surface of zeolite crystallites and pore blockage [54], the poisoning ability of bulkier nitrogen bases is even higher [52,55]. Xu et al [56][57][58][59][60] demonstrated that N-heterocycles (pyridines, pyrroles, anilines and indoles) can be produced via reaction of biomass derived oxygenates and ammonia. Even though not measured directly, some ammonia may be produced from the FP of wheat straw containing ∼1 wt% N (d.b.)…”
Section: Discussionmentioning
confidence: 99%
“…The high number of papers that cover lignin valorization, which have been identified by this work, introduces the research advances in the whole processing: the improvements in isolation, recovery, and characterization of lignin from biomass, the posterior depolymerization of lignin into monomers by chemical and biological means, and the final upgrading of the depolymerized lignin monomers to industrially relevant chemicals [41]. All these aspects have been deeply described by several reviews [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], and, therefore, the purpose of this section is just to summarize the most The most frequently selected keyword was Lignin, with 245 appearances. As Lignin was one of the words employed in the search engine, it is quite logical to find it among the most common keywords.…”
Section: Review Of the Main Alternatives For Lignin Valorization And mentioning
confidence: 95%
“…Lignin, the second most abundant biomacromolecule next to cellulose, is proven to be synthesized through specific biosynthesis pathways. , As a complicated three-dimensional network polymer, lignin plays a significant role in plant cell walls between cellulose and hemicellulose by lignin–carbohydrate complex (LCC) linkages, , providing mechanical strength and structural support, as shown in Figure a . Lignin exhibits heterogeneous chemical structures depending on the types and amounts of phenylpropane subunits ( p -hydroxyphenyl, guaiacyl, and syringyl) and interunit linkages (ether linkage and C–C bonds), such as β- O -4, β-β, β-5, and β-1 linkages in Figure b, c. Nevertheless, the native structure of lignin has been confirmed by ceaselessly intensive research using state-of-the-art analytical technology, especially nuclear magnetic resonance (NMR) technology. …”
Section: Physical and Chemical Properties Of Technical Ligninmentioning
confidence: 99%